2013
DOI: 10.1038/nchem.1817
|View full text |Cite|
|
Sign up to set email alerts
|

Discrimination of epimeric glycans and glycopeptides using IM-MS and its potential for carbohydrate sequencing

Abstract: Mass spectrometry is the primary analytical technique used to characterize the complex oligosaccharides that decorate cell surfaces. Monosaccharide building blocks are often simple epimers, which when combined produce diastereomeric glycoconjugates indistinguishable by mass spectrometry. Structure elucidation frequently relies on assumptions that biosynthetic pathways are highly conserved. Here, we show that biosynthetic enzymes can display unexpected promiscuity, with human glycosyltransferase pp-α-GanT2 able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
172
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(174 citation statements)
references
References 39 publications
1
172
1
Order By: Relevance
“…In order to confirm this, we analyzed selected glycosides by ion-mobility MS (IM-MS), a rapid and sensitive technique that separates gas phase ions based on their mobility (inversely proportional to a molecules collision cross-section area) as they traverse through an inert buffer gas [33, for review see 34]. IM-MS has been previously reported as being able to discern the identity of hexose residues based on the arrival time distribution (ATD) of monosaccharide product ions, generated by collision-induced dissociation (CID) of either glycopeptides or free reducing-saccharides [17]. Recently it has also been shown that IM-MS has the potential to discern the stereo-/regio-chemistry of the glycosidic bond of glucose oligosaccharides, based on the ATDs of these monosaccharide product ions compared to synthetic standards (C.J.…”
Section: Ion-mobility Ms Characterization Of Cyanogenic Glycosides Anmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to confirm this, we analyzed selected glycosides by ion-mobility MS (IM-MS), a rapid and sensitive technique that separates gas phase ions based on their mobility (inversely proportional to a molecules collision cross-section area) as they traverse through an inert buffer gas [33, for review see 34]. IM-MS has been previously reported as being able to discern the identity of hexose residues based on the arrival time distribution (ATD) of monosaccharide product ions, generated by collision-induced dissociation (CID) of either glycopeptides or free reducing-saccharides [17]. Recently it has also been shown that IM-MS has the potential to discern the stereo-/regio-chemistry of the glycosidic bond of glucose oligosaccharides, based on the ATDs of these monosaccharide product ions compared to synthetic standards (C.J.…”
Section: Ion-mobility Ms Characterization Of Cyanogenic Glycosides Anmentioning
confidence: 99%
“…Samples were analysed according to the protocol reported by Both et al [17]. Briefly, plant glycosides were diluted to approx.…”
Section: Im-ms/ms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in a study of the analysis of epimeric glycans with ion-mobility mass spectrometry, the presence of a single axial hydroxyl substituent on an aldohexose monosaccharide was hypothesized to lead to a lack of discrimination, as in the case of galactose (C4) versus mannose (C2) [6]. This single axial hydroxyl theory, however, does not hold in this fixed ligand method described.…”
Section: Resultsmentioning
confidence: 99%
“…However, carbohydrate sequencing has significantly lagged capabilities in sequencing nucleic acids and proteins. Compared with these other biomolecules, polymers and oligomers of carbohydrates are more structurally complex because of their large range of stereochemical differences, absolute configuration (D or L), anomeric configurations (α or β), and linkage positions [2,4,6,7]. This high degree of structural complexity has hindered accurate structural analyses of glycans, so much so that a United States National Academy of Sciences report issued in 2012 has called for the development of technology over the next 10 years to purify, identify, and determine the structures of all the important glycoproteins, glycolipids, and polysaccharides in any biological sample [8].…”
mentioning
confidence: 99%